Novel Expression Patterns of Metabotropic Glutamate Receptor 6 in the Zebrafish Nervous System - Huang, Ying-Yu; Haug, Marion F.; Gesemann, Matthias; Neuhauss, Stephan C. F. (PLOS ONE, 2012)
The metabotropic glutamate receptor 6 (mGluR6 or GRM6) belongs to the class III of the metabotropic glutamate receptor family. It is the only known mGluR that mediates direct synaptic transmission in the nervous system and is thought to mediate the ON-response in the ON-pathway of the vertebrate retina. Phylogenetic and gene structure analysis indicated that the zebrafish genome harbours two mglur6 paralogs, mglur6a and mglur6b. Besides expression in the inner nuclear layer and distinct regions in the brain, both mglur6 paralogs are expressed in ganglion cells of the retina, an expression pattern which can also be observed in the downstream effector molecules gnaoa and gnaob. This unexpected expression pattern is consistent with immunohistological labeling using a peptide antibody specific for the mGluR6b paralog. These expression patterns contradict the existing view that mGluR6 is solely located on ON-bipolar cells where it functions in signal transmission. Consistent with expression in ON-bipolar cells, we report a decreased b-wave amplitude in the electroretinogram after morpholino-based downregulation of mGluR6b, showing a function in the ON response. Our data suggest more widespread functions of mGluR6 mediated signaling in the central nervous system, possibly including sign reversing synapses in the inner retina.